Ethical Decision Making: The Effects of Escalating Commitment - Street, Marc D. (Journal of business ethics, 1997)
Despite the recent emergence of many new ethical decision making models, there has been minimal emphasis placed on the impact of escalating commitment on the ethical decision making process. In this paper a new variable is introduced into the ethical decision making literature. This variable, exposure to escalation situations, is posited to increase the likelihood that individuals will choose unethical decision alternatives. Further, it is proposed that escalation situations should be included as a variable in Jones's (1991) comprehensive model of ethical decision making. Finally, research propositions are provided based on the relationship between escalating commitment and the ethical decision making process.